43 : Inside the George W. Bush Presidency - Riley, Russell L. (Russell Lynn), 1958-; Perry, Barbara A. (Barbara Ann), 1956-; Nelson, Michael, 1949- (Book collections on Project MUSE., 2022)
"The presidency of George W. Bush has been the subject of extensive commentary but limited scholarly analysis in the years since he left office. 43 addresses this by drawing on-without relying on-the recently released interviews of the Miller Center's Presidential Oral History Program. The volume consists of ten chapters, written by highly regarded presidential scholars, examining key topics and themes, including 9/11, the unitary executive, compassionate conservatism, Cheney's vice presidency, the Iraq War, and the financial crisis"--